Chemical constituents from stem bark of Flacourtia rukam zoll. & mor. and their antioxidant activities - Muharni; Elfita; Heni Yohandini; Julinar; Yasrina; Miranti (Penerbit Universiti Kebangsaan Malaysia, 2019)
Exploration of chemical compounds and biological activities of extract stem bark of Flacourtia rukam have been succesfully. We have isolated and characterized three compounds friedelin (1), poliothrysoside (2), and β-sitosteryl-3β-glucopyranoside (3). The structures were identified used UV, IR and NMR spectrum data and comparison of their NMR data with literature. The antioxidant activities of each of them were tested used DPPH (1,1-diphenyl-2-picryl hydrazyl) method. All compounds givn IC50 value >100 μg/mL and were categorized weaker antioxidant. Compounds 2 and 3 have been reported from other species from genus Flacourtia but this is the first report of the isolation from F. rukam.